The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1093/jac/40.3.353
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of spiramycin and metronidazole alone or in combination against clinical isolates from odontogenic abscesses

Abstract: One hundred and forty-eight isolates of bacteria from 20 intraoral odontogenic abscesses were tested for their susceptibility to spiramycin and metronidazole alone or in combination. All isolates, except Rothia spp. (one), Enterococcus avium (three), Haemophilus parainfluenzae (one) and Staphylococcus aureus (one) were sensitive to spiramycin and/or metronidazole. Among the anaerobes, spiramycin as well as metronidazole showed good antimicrobial activity against species of Prevotella, Eubacterium, Peptostrepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 0 publications
1
23
0
5
Order By: Relevance
“…In mixed infections, strict anaerobes outnumber facultatives by a ratio which varies between 1.5-3 : 1, again depending on the recovery and culture conditions Khemaleelakul et al, 2002;Kulekci et al, 1996;Lewis et al, 1993;Roche & Yoshimori, 1997;Sakamoto et al, 1998). The mean number of species recovered by culture from dentoalveolar aspirates is 4 with a range of between 1 and 7.5 (Fazakerley et al, 1993;Khemaleelakul et al, 2002;Reader et al, 1994).…”
Section: Cultural Analysis Of the Acute Dental Abscessmentioning
confidence: 99%
See 1 more Smart Citation
“…In mixed infections, strict anaerobes outnumber facultatives by a ratio which varies between 1.5-3 : 1, again depending on the recovery and culture conditions Khemaleelakul et al, 2002;Kulekci et al, 1996;Lewis et al, 1993;Roche & Yoshimori, 1997;Sakamoto et al, 1998). The mean number of species recovered by culture from dentoalveolar aspirates is 4 with a range of between 1 and 7.5 (Fazakerley et al, 1993;Khemaleelakul et al, 2002;Reader et al, 1994).…”
Section: Cultural Analysis Of the Acute Dental Abscessmentioning
confidence: 99%
“…However, a number of more recent studies have indicated that staphylococci may indeed be a more frequent colonizer of the oral tissues than previously thought (Smith et al, 2001). The recovery rates using conventional culture of Staphylococcus aureus from the acute dental abscess range from 0.7 to 15 % (Brook et al, 1991;Goumas et al, 1997;Kulekci et al, 1996;Kuriyama et al, 2002b;Roche & Yoshimori, 1997;Siqueira et al, 2001d) although some workers have noted higher recovery rates of 47 % (Mangundjaja & Hardjawinata, 1990). Interestingly, Staphylococcus aureus has been reported to occur more frequently in severe dental abscesses from children (Brook et al, 1991;Coticchia et al, 2004;Coulthard & Isaacs, 1991;Dodson et al, 1989;Tan et al, 2001).…”
Section: Facultative Anaerobesmentioning
confidence: 99%
“…Dentoalveolar abscesses are almost always caused by a polymicrobial flora of aerobic, facultatively anaerobic, and anaerobic bacteria (7,20). Abscesses in the maxillofacial region result either from infections around the apices of teeth via a necrotic pulp or from bacterial invasion of the surrounding tissues via the periodontal margin (9,22).…”
mentioning
confidence: 99%
“…L'association spiramycine + métronidazole a été largement utilisée. L'activité de cette association sur les anaérobies de la flore buccale avait été évaluée en 1997 [2] ; il apparaissait indispensable que cette association fasse l'objet d'une nouvelle évaluation. De plus, ces antibiotiques recommandés n'ont jamais été étudiés simultanément.…”
unclassified
“…Le but de cette étude est donc de déterminer les CMI de 3 macrolides à 14, 15 et 16 atomes (respectivement l'érythromycine, l'azithromycine et la spiramycine), d'une lincosamide (clindamycine), d'une streptogramine (pristinamycine), du métronidazole, de l'association spiramycine + métronidazole (2/1) et de l'amoxicilline seule ou associée à l'acide clavulanique sur un collectif de 104 souches anaéro-bies isolés à partir de cellulites d'origine dentaire et dans deux tiers des cas de poches parodontales. En comparant les CMI de l'association spiramycine + métronidazole aux CMI de la spiramycine et du métronidazole, il sera possible de voir si l'association est additive, antagoniste ou synergique comme le montrent plusieurs études antérieures [2,3] .…”
unclassified